التأويل السيميائي بين مقصديّة المتكلّم و حدود المؤول - عوض, سامي; يوسف, ميساء (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The main aim of semiotics is to reach the real meaning in a context as words denote more than one meaning, saying more than what the speaker wants to say. Simply, they are not neutral in delivering the meaning but rather they are one way to understand the speaker’s internal thoughts and intentions which are not reachable through lines. However, you may reach these thoughts by interpreting the sings in a particular text and the way they are linked together. In semiotics, there are many different ways to interpret signs, yet the real meaning of a text is fixed and there is no way to add to or change within it; what differs is the significance. Every reader interprets a text as he thinks of it and as the text itself aims to. However, the reader is restricted in his interpretations as theinterpretations of any text are not in random and there are limits at which the reader should stop to guarantee that his interpretation is correct. In brief, this research tries to define specific types of interpreters to reach defined limits to interpret a text.إنّ الهدف الذي تروم السيميائيات الوصول إليه هو بناء المعنى المتشكّل ضمن البنية العميقة للنصّ ، فالكلمات تقول أكثر مما يريده مرسلها أن تقوله ، إنّها و بكلّ بساطةٍ ليست حياديّة في نقل المعنى ، و إنّما لها دور في الكشف عن فكر المرسل ، و خبايا نفسه ، التي لا يمكن الوصول إليها إلاّ بوساطة التأويل ، المستند إلى علامات النّص،وترابطها ، و انسجام بعضها مع بعض ، وهي تنقل المعنى الذي يريده مرسلها . و طرائق تأويل العلامات في السيميائيات متعددة و متشعّبة بتشعّب السيرورة الدلاليّة التي تولد و تتنامى بفعل الإحالات اللانهائيّة التي تحيلُ عليها ، مع ملاحظة أنّ معنى النّص ثابتٌ من خلال تجليه الخطي ، و غير قابل للإضافة أو التغيير ؛ لكنّ الذي يتغير هو الدلالة التي يمنحها كلّ قارئ و مؤول لهذا النّص حسب مقاصده هو ، و مقاصد النّص ؛ لكنّه بتأويله هذا ليس حرّاً بشكلٍّاعتباطيّ إنّما هناك آليات و حدود يجب التوقّف عندها لضمان صحة هذا التأويل .و من هنا ، سعى البحث لتحديد أنواع المؤولين ، بهدف الوصول إلى ضوابط لتأويل النصوص .